Calculation Model and Case Study of Water-Saving Quantity in Typical Industrial Enterprises - Chunyan Zhu; Mengting Hu; Xue Bai; Lan Zhang (Journal of Applied Mathematics)
Water-saving quantity is an important index to measure the effect of water saving. Scientific calculation of water-saving quantity is a basic content of water saving work, and is also an important means to carry out water saving evaluation and guide industrial enterprises to use water reasonably. This paper puts forward that the connotation of water saving is the improvement of water efficiency. Based on this, the calculation model of water saving in typical industrial enterprises is constructed. The water-saving quantity of textile enterprises and beverage production enterprises before and after water-saving technological transformation is calculated, which provides a reference for the calculation of water saving in typical industrial enterprises.